Onset of suffusion in upward seepage under isotropic and anisotropic stress conditions. Issue 12 (2nd December 2019) - Liang, Yue; Yeh, Tian-Chyi Jim; Wang, Junjie; Liu, Mingwei; Zha, Yuanyuan; Hao, Yonghong
Abstract: Suffusion is one of the mechanisms initiating internal erosion in levees and dams. To estimate the risks of seepage erosion, understanding the mechanism of suffusion under different stress conditions is crucial. With a stress-controlled apparatus, experiments are conduced, in which suffusion is induced by step-wise increasing hydraulic gradients under the isotropic and the anisotropic stress conditions. Based on the results, a low critical hydraulic gradient (LCHG) and a high critical hydraulic gradient (HCHG) are defined, corresponding to the local and the global mobilisations of fine particles, respectively. It is found that the critical hydraulic gradients under isotropic and anisotropic stress conditions are remarkably different. Under the isotropic stresses, the critical hydraulic gradients increase monotonously with the confining stress. Whereas, under the anisotropic stress conditions, the critical hydraulic gradients increase at first and then decrease after reaching a maximum value. A microscopic scale conceptual model attributes this difference to the shear stress, created by the deviatoric stresses. In the end, a formula is proposed to estimate the critical hydraulic gradients, considering the effects of the stress conditions. The accuracy of the formula is verified by comparing the experiment results and the prediction by the formula.